Determinan Keterlambatan Laporan Audit dengan Spesialisasi Industri Auditor sebagai Variabel Moderasi - Mella Devina Sari; Indah Anisykurlillah (Politeknik Ganesha Medan, 2026)
This study examines the determinants of audit report lag (ARL) by emphasizing the moderating role of auditor industry specialization in strengthening or weakening the relationship between audit tenure, earnings volatility, and investment opportunity set. This study addresses the inconsistency of prior findings by positioning auditor industry specialization as a contingent factor that may influence audit efficiency. This research utilizes a quantitative methodology and analyzes secondary data from companies in the basic materials sector that are listed on the Indonesia Stock Exchange (IDX) for the years 2021 to 2024. . The samples selected through purposive sampling method include 180 observational data analyzed by multiple linear regression and Moderated Regression Analysis (MRA) with the help of EViews software. The results show that audit tenure and earnings volatility have a negative effect on audit report lag, while investment opportunity set has no significant effect. More importantly, this study finds that auditor industry specialization only moderates the relationship between earnings volatility and audit report lag, but does not moderate the effects of audit tenure and investment opportunity set. These findings highlight that the effectiveness of auditor industry specialization is contingent upon the complexity of financial information, particularly earnings volatility. The novelty of this study lies in providing empirical evidence that auditor specialization does not universally act as a strengthening mechanism, but rather operates selectively depending on the characteristics of the audited variable. This study contributes to the audit literature by clarifying the conditional role of auditor industry specialization and provides practical implications for auditors, regulators, and firms in improving audit timeliness